A PRELIMINARY STUDY ON THE UNDERSTANDING OF ISLAMIC BUSINESS ETHICS AMONG HAWKERS OF SAIMOR PATTANI, THAILAND - Farok Zakaria (Journal of Islamic, Social, Economics and Development, 2021)
Business ethics is one of the areas of concern when one discusses about the management and outcome of running a business. This aspect is even important for a Moslem business since it is bind to the principle of Islam in making a business. Business in Islam regardless of size and type must follow suit all the principles related to business in Islam such as no cheating in weighing, selling halal items, diligent, always tawakkal to Allah and many other Islamic business behavior. In Islam it is considered as Fardhu Kifayah for Moslem to engage in business if it really needed by fellow Moslems. In relation to that, many Moslems in Pattani have chosen entrepreneurship or doing business as their career path and the question here is are they really/ strictly follow the ethic of Islamic businesses in their daily business operations. A total of 25 small street hawkers were interviewed on what they understand and practice with regards to Islamic business ethics. It was found that most of the hawkers viewed halal, not cheating and wearing Moslem clothing as Islamic business ethics. Others like working hard and tawakkal to Allah is considered as something that as the least remembered Islamic values that they should hang on. This paper presents the findings on how small businesses at the flourishing street of Moor or popularly known as Saimoor perceive Islamic business ethics and discusses some possible actions to better guide those business owners in obeying Islamic business ethics.